Game Edukasi Visual Novel Bermain Pantun dan Peribahasa Menggunakan Ren'py Berbasis Python - Orita Dwi Purbiyanti; Sepitri Daruyani; Irawaty Irawaty; Adellia N. Adyna Putri Irawan (Journal of Computer System and Informatics (JoSYC), 2022)
In the digital era, technological developments, especially games, are very promising to learn. This can be used as an interactive learning tool for every game fan. Learning media using games can be an alternative for elementary school students to get to know rhymes and proverbs easily and fun. An interactive program that can arouse students' interest in knowing rhymes and proverbs is needed to eliminate boredom when studying them. The researcher uses the SDLC method to create a visual novel game application to play rhymes and proverbs with Python-based Ren'py. Learning to play rhymes and proverbs through visual novels is done by choosing from different problems from the novel's plot. The results obtained in making this game is an interactive novel game by displaying each dialogue which can then be answered by the user and the selected dialogue can determine the flow of the game.